Dwarfs in Ancient Indian Religious Iconography: The Levels of Interpretation - Vorob’eva, Darya N. (Actual Problems of Theory and History of Art, 2017)
The images of dwarfish beings inhabit ancient Indian temples in great abundance. One has only to look carefully to start noticing them everywhere: in mythological scenes and decorative friezes, in prabhamandala around the object of veneration and as bhadrakaras — original atlantes, supporting architectural elements; on walls, pillars and ceilings, in the interiors and on the facades of temples. This pan-Indian image is common in iconographic program of Hinduism, Buddhism, and Jainism, the three major religions of ancient India. Despite similar appearance, the figures of dwarfs may be interpreted in completely different ways, as different characters.The meaning depends on the location in the iconographic program, their attributes, weapons, posture, gestures, and encirclement. They are demonic creatures and guardians, fearful and worshipful at the same time. They arecajoled and addressed with specific requests concerning different needs: well-being, harvest, as well as granting children. However, only one value is determined by the iconography of temple dwarfs images, their semantics is much more complicated as religious images tend to have more than one meaning and can be understood onmany levels, corresponding to different research perspectives. The figures of dwarfs play a minor but important role in the ancient Indian religious iconography.